Predicting Sea-level Rise and Infrastructure Effects on Coastal Wetlands - Rodriguez, Jose F. (2017)
: Climate change predictions for Australia include an accelerated sea-level rise, wich challenges the survival of estuarine wetlands. Furthermore, coastal infrastructure poses and additional constraint on the adaptive capacity of these ecosystems. This paper presents results of wetland evolution based on hydro period and inundation depth experienced by vegetation, and computed using a hydrodynamic model. The application simulates the long-term evolution of wetland on the Hunter Estuary heavily constricted by infrastructure that is undergoing the effects of predicted accelerated sea-level rise. The wetland presents a vegetation zonation sequence mudflats –mangrove –saltmarsh from the seaward margin, but it also affected by compartmentalization due tu internal road embankments and culverts that effectively attenuates tidal inputs. Results of the modelo show that flow attenuation can play a major role in wetland hydrodynamics and that its effects can increase wetland vulnerability under climate change scenarios, particularly in situations where existing infrastructure affects the flow.